Demographic and clinicopathological profile of oral squamous cell carcinoma patients of North India: A retrospective institutional study - Aanchal Tandon; Bharadwaj Bordoloi; Rohit Jaiswal; Abhinav Srivastava; Rajeev Bhushan Singh; Uzma Shafique (Wolters Kluwer Medknow Publications, 2018)
Background: Oral cancer is one of the ten most common cancers in the world. In India, it is the most common cancer among male and the third most common among female population. Objective: The aim of this study was to evaluate retrospectively the epidemiologic profile of patients with oral squamous cell carcinoma (OSCC). Method: The study sample comprised of ninety eight biopsies diagnosed as OSCC. The clinical and histopathological features were analyzed using descriptive statistics, Student's t test and chi-square test. Results: Male to female ratio was 3.26:1. Mean age was 51.35 ± 14.39 years and 55.35 ± 8.87 years in males and females, respectively. The most common site of occurrence was buccal mucosa and gingivo-buccal sulcus (GBS). Most of the cases (66.32%) were well-differentiated OSCC. In most of the cases (66.32%) the diagnosis was made within 2-6 months of onset of symptoms. Conclusion: In India, OSCC is a major health problem. Strategies must be made to improve the present scenario of health care service, where Government-run health care centers are burdened with ever-increasing patient pool and to avail treatment in such centers is always a compromise with time and health. Effective oral health programs for spread of knowledge and awareness, prevention, early diagnosis and management, and follow up of oral cancer must be implemented.